2009
DOI: 10.4049/jimmunol.0803951
|View full text |Cite
|
Sign up to set email alerts
|

Mast Cell-Dependent Contraction of Human Airway Smooth Muscle Cell-Containing Collagen Gels: Influence of Cytokines, Matrix Metalloproteases, and Serine Proteases

Abstract: In asthma, mast cells infiltrate the airway smooth muscle cell layer and secrete proinflammatory and profibrotic agents that contribute to airway remodeling. To study the effects of mast cell activation on smooth muscle cell-dependent matrix contraction, we developed coculture systems of human airway smooth muscle cells (HASM) with primary human mast cells derived from circulating progenitors or with the HMC-1 human mast cell line. Activation of primary human mast cells by IgE receptor cross-linking or activat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
31
0
2

Year Published

2009
2009
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(34 citation statements)
references
References 67 publications
1
31
0
2
Order By: Relevance
“…For example, mast cells can influence the behaviour of nerve cells, the first cell type recognized as a target of mast cell signals, through products such as histamine (and serotonin in the case of mouse mast cells) 27 . Mast cells also communicate with smooth muscle cells 63 . Together, these interactions could potentially promote the elimination of pathogens from the body, such as that which occurs during mast cell-promoted expulsion of bacteria and fluids from the gut in response to cholera and clostridium toxins 64,65 .…”
Section: Innate Immune Functions Of Mast Cellsmentioning
confidence: 99%
“…For example, mast cells can influence the behaviour of nerve cells, the first cell type recognized as a target of mast cell signals, through products such as histamine (and serotonin in the case of mouse mast cells) 27 . Mast cells also communicate with smooth muscle cells 63 . Together, these interactions could potentially promote the elimination of pathogens from the body, such as that which occurs during mast cell-promoted expulsion of bacteria and fluids from the gut in response to cholera and clostridium toxins 64,65 .…”
Section: Innate Immune Functions Of Mast Cellsmentioning
confidence: 99%
“…It has also been shown that MC proteases can activate yet other MMPs. [80][81][82] Potentially, MC protease-mediated ECM modification could lead to a more efficient influx of inflammatory cells into the tissue and to effects on cellular adhesion to the ECM. It is also noteworthy that degradation of the ECM can unleash proinflammatory cleavage products, such as fibronectin fragments or chemokines/growth factor bound to proteoglycans present in the ECM.…”
Section: Effects On Ecmmentioning
confidence: 99%
“…Quantitation from densitometric analysis for phospho-protein signals was normalized by cell numbers seeded. Fold change over control conditions is indicated for representative experiments as stated in the ''Materials and methods'' section (HFL-1) [41] or human airway smooth muscle cells (HASM) [48], as a model for remodeling changes associated with asthma. To examine functional consequences of the synergistic activation of HMC-1 by IL-33 and SCF, HMC-1 cells were co-embedded in collagen gels with either HFL-1 or HASM, and contractile responses were measured as a decrease in gel surface area.…”
Section: Il-33 and Adenosine Receptor Co-stimulation Induces An Erk-dmentioning
confidence: 99%